Efficacy and Safety of Faecal Microbiota Transplantation for Acute Pancreatitis: A Randomised, Controlled Study - Ding, Ling; He, Cong; Li, Xueyang; Huang, Xin; Lei, Yupeng; Ke, Huajing; Chen, Hongyan; Yang, Qinyu; Cai, Yan; Liao, Yuanhang; He, Wenhua; Xia, Liang; et al. (Frontiers in Medicine, 2022)
Abstract Aims: We investigated whether faecal microbiota transplantation (FMT) decreases intra-abdominal pressure (IAP) and improves gastrointestinal (GI) dysfunction and infectious complications in acute pancreatitis (AP). Methods: In this first randomized, single-blind, parallel-group, controlled study, we recruited and enrolled consecutive patients with AP complicated with GI dysfunction. Eligible participants were randomly assigned to receive faecal transplant (n=30) or normal saline (n=30) via a nasoduodenal tube once and then again two days later. The primary endpoint was the rate of IAP decline; secondary endpoints were GI function, infectious complications, organ failure, hospital stay and mortality. Analyses were based on intention to treat. Results: We enrolled 60 participants and randomly assigned them to the FMT (n=30) or control (n=30) group. Baseline characteristics and disease severity were similar for both groups. IAP decreased significantly one week after intervention in both groups, with no difference in the IAP decline rate between FMT and Control group (0.1 (-0.6, 0.5) vs. 0.2 (-0.2, 0.6); P=0.27). Normal gastrointestinal failure (GIF) scores were achieved in 12 (40%) patients in the FMT group and 14 (47%) in the control group, with no significant difference (P=0.60). However, D-lactate was significantly elevated in the FMT group compared to the control group, as calculated by the rate of IAP decline (-0.3 (-3.7, 0.8) vs. 0.4 (-1.1, 0.9); P=0.01). Infectious complications occurred in 15 (50%) and 16 (53.33%) patients in the FMT and control groups, respectively (P=0.80). However, interleukin-6 (IL-6) was significantly elevated in the FMT group compared to the control group, as calculated by the rate of IAP decline (0.4 (-3.6, 0.9) vs. 0.8 (-1.7, 1.0); P=0.03). One participant experienced transient nausea immediately after FMT, but no serious adverse events were attributed to FMT. Conclusion: FMT had no obvious effect on IAP and infectious complications in AP patients, though GI barrier indictors might be adversely affected. Further multi-centre studies are needed to confirm our findings. The study was registered at https://clinicaltrials.gov (NCT02318134).